Anther Culture in Cocoa - Sunil K P (Department of Agricultural Botany, College of Horticulture, 1992)
Investigations on anther culture of cocoa (Theobroma cacao L.) were carried out at the College of Horticulture, Kerala Agricultural University, Vellanikkara, during 1990-'92 with the objective of studying the amenability of cocoa anther under in vitro conditions for the production of haploids. The fertility and viability of pollen grains of cocoa were found to be 35 and 61 per cent respectively. Anthers at tetrad stage (bud length 1.75 mm) were subjected to a two-stage culture procedure involving incubation and subculture (after 4 weeks) on modified H3 basal medium supplemented with 1 mg 1-1 NAA and 0.1 mg 1-1 2-iP for 50 days (stage 1) and subsequent weekly transfer to ½ Ms basal media supplemented with 0 to 1 mg 1-1 2-iP and 0 to 3 mg 1-1 GA3 (stage II). Proembryoids were obtained in stage 1 medium via callus within 45 days of culture, only when anthers derived from Criollo, Trinitario and H2 were cultured. Serial subculturing of embryoids in stage II media led to formation of shootlets and rootlets. With four sub- cultures in stage II in a span of one month, the embryoids could be germinated into plantlets of size 2.5 cm with two leaflets and one rootlet. This is the first report of plantlet recovery from cocoa anthers via indirect embryogenesis. The plantlets were dried up after an elapse of 3 months. The most favourable combination for root development was Ms medium supplemented with 2 mg 1-1 2-iP, 0.1 mg 1-1 NAA and 126 mg 1-1 PG.